Efeitos da suplementação de taurina ou flavonóides de cacau associado à achocolatado sobre a composição corporal, metabolismo de carboidratos e proteinas, desempenho fisico, dano muscular e estresse oxidativo em atletas - Carvalho, Flávia Giolo de [UNESP] (2015)
BACKGROUND: Taurine is a nitrogenous compound, which has several beneficial physiological effects like antioxidant action, and could increase muscle force contraction and insulin sensibility. Triathlon is a sport of medium to high intensity, that can increase oxygen consumption rate during intense exercise and consequently raise free radicals production and oxidative stress, which may compromise an athlete's performance. Due to the weekly intense training, triathletes need nutritional care ranging from calories and nutrients adequacy to the use of specific nutrients that can help to maintain health. Thus, it is believed that the use of taurine associated with chocolate milk after exercise can promote general metabolic insulin action in order to favor carbohydrates metabolism regulation, assist muscle recovery, improve glycogenesis, prevent oxidative damage and thus promote triathletes performance and muscle mass gain. OBJECTIVE: Evaluate the effects of taurine and chocolate milk supplementation in body composition, athletic performance, protein metabolism and oxidative stress in triathletes. METHODS: A double-blind, crossover, 2-week washout study was conducted with 10 male triathletes, aged 25 to 35 years, which capsules containing three grams of taurine or placebo and 400 ml of chocolate milk ready to drink was offered during eight weeks. In order to assess the effects of supplementation urinary nitrogen, creatinine and urea, and plasmatic glucose, insuline and oxidative stress markers (MDA, GSH and vitamin E) were quantified. Body composition was measured by the method of deuterium labeled water. The evaluations occurred in four stages: 1o - before starting the training season; 2o - after 8 weeks of training; 3o- before starting the second training season and 4o- after 8 weeks of training and supplementation completion. Data were organized according to the study ...